The Effects of the Position Changes of Critical Care Patients on Respiratory and Cardiac Parameters - İsa Kılıç; İlkay Ceylan; Derya Karasu; Sinan Gürsoy (Türk Yoğun Bakim Derneği Dergisi)

(untitled)
Objective:Position changes in patients requiring critical care aimed to mobilise secretions, prevent compression wounds and decrease the risk of ventilator-related pneumonia. This study aimed to investigate the effects of supine, left lateral, right lateral and Fowler positions on the respiratory and cardiac parameters with the CO2 rebreathing technique using non-invasive cardiac output monitor.Materials and Methods:Forty patients aged 18-65 years who were on invasive mechanical ventilator support and had a hospitalisation time >24 h were included in the study. Cardiac output was monitored with non-invasive cardiac output monitor. Patients were assisted on supine, left lateral, right lateral and Fowler positions. Respiratory and hemodynamic parameters of patients were measured at these positions with 1-h intervals.Results:A significant difference was found among the measurements when the mean arterial pressure values measured at different times at the left lateral position were compared. Similarly, a significant difference was noted among SpO2 values measured at the supine position at different times. However, this difference was not clinically significant. No significant differences were found within the groups as regards to other respiratory and cardiac parameters.Conclusion:Position changes did not lead to a clinically significant change on respiratory mechanics, hemodynamic parameters and oxygenation in patients with stable hemodynamic who were on mechanical ventilator support.